Combined force injury of the elbow joint--the mechanism clarified. Issue 4 (December 1979) - McLatchie, G. R.; Miller, J. H.; Morris, E. W.
Abstract : An unusual elbow injury occurring as a result of a poorly executed breakfall in judo is recorded. The treatment, possible mechanism and outcome are described. The poor prognosis of severe lesions is emphasised with reference to current literature.